Here's another interesting formula for finding fibonacci numbers, this one using only fn-1 and n:

fn = (fn-1 + sqrt(5fn-12 - 4(-1)n)/2

With f0 defined as 0.

The derivation for this is fairly straightforward.

First, it needs to be shown that fn+1fn-1 - fn2 = (-1)n for all n, without using the function above. It's easy to establish that for n=1, 1*0 - 1*1 = -1 = (-1)1. Since fn+1 = fn-1 + fn, fn+1fn-1 - fn2 is equivalent to fn-12 + fnfn-1 - fn2, which equals fn(fn-1 - fn) + fn-12. Replacing fn-1-fn with -fn-2 gives fn-12 - fnfn-2. In other words, letting g(n) = fn+1fn-1 - fn2, g(n) = -g(n-1), and so by induction on n, g(n) = (-1)n for all natural numbers n.

Since fn+1 = fn + fn-1, fn-1(fn + fn-1) - fn2 = (-1)n by the equation above. Simplifying to get everything on one side yields: fn2 - fn-1fn - fn-12 + (-1)n = 0. Using the quadratic formula on that gives the equation for fn in terms of fn-1 and n.

This formula makes the relation between the fibonacci numbers and the golden mean very apparent without actually using the golden mean at any point, which seemed pretty interesting to me when I first learned of it.